HUBUNGAN KECERDASAN SPIRITUAL DENGAN MINAT BELAJAR PADA SISWA KELAS IV PEMBELAJARAN TEMATIK - Wibowo, Dwi Cahyadi; Tino, Milennianto; Sirhi, Sirilus; Rusdi, Rusdi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of this research is to determine the relationship between spiritual intelligence and interest in learning in class IV students at SD Negeri 01 Sui. Ukoi. The method used is a quantitative method, with a form of correlation research. The research population came from fourth grade students using saturated sampling. Based on the results of the spiritual intelligence questionnaire, an average of 83.12 was obtained in the very good category. Meanwhile, students' interest in learning was obtained on average 71.48, which is included in the good category. Based on the calculation results from the significant test analysis, tcount>ttable is 3.807 > 2.069. Thus, based on the test criteria that have been determined, Ho is rejected and Ha is accepted. As a conclusion, there is a significant relationship between spiritual intelligence and interest in learning in fourth grade students in elementary school.